2020
DOI: 10.1002/fsn3.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbiological, chemical, and sensory properties of cooked probiotic sausages containing different concentrations of astaxanthin, thymol, and nitrite

Abstract: In this study, the effects of different concentrations of thymol and astaxanthin on control of Clostridium perfringenes and also microbial, chemical, and organoleptic properties of common and probiotic beef cooked sausages containing two levels of nitrite during storage at refrigerated condition during 45 days were evaluated. Based on findings, control group had significantly higher total volatile base nitrogen (TVB‐N) than nitrite‐, thymol‐, and astaxanthin‐treated samples. At the end of the storage time in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The decrease in AST may lead to an increase in bacterial growth activity, accelerating the spoilage process of meat products, which corresponds to the increase in TVB‐N and pH levels in the present study. Mohammadpourfard et al 35 . reported that the control group exhibited considerably greater TVB‐N levels than the astaxanthin‐treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in AST may lead to an increase in bacterial growth activity, accelerating the spoilage process of meat products, which corresponds to the increase in TVB‐N and pH levels in the present study. Mohammadpourfard et al 35 . reported that the control group exhibited considerably greater TVB‐N levels than the astaxanthin‐treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the results of this study, Sepahvand et al [3] have reported that the application of thymolnanoemulsion did not improve the performance of thymol with regards to its reduction in the bacterial count within a sausage mixture. Mohammadpourfard et al [38] have similarly confirmed that thymol effectively controlled the population of C. perfringens and lactic acid bacteria in cooked probiotic sausages. In addition, Wang et al [39] have reported that chitosan nanoemulsions containing thymol reduced the proportion of spoilage organisms in fresh pork and reduced bacterial diversity.…”
Section: The Antimicrobial Activity Of Thymol and Thymol-loaded Nlc I...mentioning
confidence: 86%
“…However, H. pluvialis has been approved as a color additive and dietary-supplement in the USA, Japan, and some European countries. Astaxanthin from H. pluvialis had been granted “GRAS” status (Generally Recognized As Safe) by US FDA (Food and Drug Administration) [ 152 ]. The European Food Safety Authority (EFSA) recommended the use of 0.034 mg/kg of the bodyweight of astaxanthin.…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%